Investigation on fatigue crack propagation failure mechanism of hydraulic lifting pipe in deep‐ocean natural gas hydrate exploitation - Liang, Hao; Guo, Xiaoqiang; Chen, Xinghan; Li, Xinye (Energy science & engineering, 2024)
In deep‐ocean natural gas hydrate exploitation operation, the fatigue failure mechanism has attracted more and more attention from scholars, but it has not been effectively disclosed. Therefore, in this work, a multifield coupling and multiple‐nonlinear vibration model of lifting pipe is established, which can accurately determine the alternating stress of deep‐ocean lifting pipe. Second, according to Forman theory, the calculation method of crack propagation length and depth on the surface of a deep‐water riser is established, which is verified by the comparison between the experimental and theoretical model calculation results. The results demonstrate that, first, the effect of residual stress in the welded joint of deep‐ocean lifting pipe should be considered in the later parameter influence analysis. Second, the fatigue growth life of deep‐water pipe with small outflow velocity is mainly determined by tensile stress, and that is determined by both tensile stress and bending stress with large outflow velocity. Third, more attention should be paid to the vibration of the lower pipe on‐site to reduce its vibration frequency and vibration stress amplitude, which can effectively reduce the surface crack propagation state of the deep‐ocean pipe and improve the service life of the pipe. Fourth, properly adjusting the tension coefficient of the tensioner during field operation can effectively improve the safety of the pipe, and the optimal tension coefficient is related to the configuration of the deep‐ocean pipe system, which can be analyzed and determined by the model. During the process of lifting hydrate, the mining riser is subject to the internal gas‐liquid‐solid three‐phase flow vibration effect (the hydrate ore body naturally decomposes into natural gas due to environmental factors), the vortex vibration effect caused by external currents, the movement of the platform and its own great length‐to‐diameter ratio (the ratio of the length to the diameter is more than 1000) and other factors of the joint influence, resulting in serious accidents such as fatigue fracture of risers. In this work, firstly, a multi‐field coupling and multiple‐nonlinear vibration model of lifting pipe is established, which can accurately determine the alternating stress of deep‐ocean lifting pipe. Secondly, according to Forman theory, the calculation method of crack propagation length and depth on the surface of deep‐ocean lifting pipe is established. Then, the fatigue corrosion crack propagation test of high‐strength 13Cr‐L80 pipe material is carried out. Finally, the influences of different internal, external flow velocities, top tension and welding residual stress on the fatigue life of surface cracks in pipe‐welded joints are analyzed.